1983
DOI: 10.1111/j.1365-2125.1983.tb01500.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the in vivo effects of ketotifen, clemastine, chlorpheniramine and sodium cromoglycate on histamine and allergen induced weals in human skin.

Abstract: 1 The effect of ketotifen was compared with that of clemastine and chlorpheniramine, known antihistamines, and sodium cromoglycate, a drug considered to have mast cell 'stabilizing' properties on histamine and allergen wealing reactions in human skin, in random order, double-blind, placebo controlled studies. 2 Ketotifen was significantly more potent in the inhibition of both histamine (P < 0.001) and allergen (P < 0.001) skin wealing reactions than either clemastine or chlorpheniramine. Sodium cromoglycate ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…Indeed we have previously shown that clemastine and ketotifen are more potent antihistamines than chlorpheniramine at least in human skin (Phillips et al, 1983). This is the first study in which ketotifen has been administered topically on to the nasal mucosa.…”
Section: Drug Studymentioning
confidence: 79%
See 3 more Smart Citations
“…Indeed we have previously shown that clemastine and ketotifen are more potent antihistamines than chlorpheniramine at least in human skin (Phillips et al, 1983). This is the first study in which ketotifen has been administered topically on to the nasal mucosa.…”
Section: Drug Studymentioning
confidence: 79%
“…This is the first study in which ketotifen has been administered topically on to the nasal mucosa. This drug has been shown to possess powerful antihistaminic effects both in vitro and in vivo (Martin & Roemer, 1978;Phillips et al, 1983). The lack of a significant inhibitory effect of ketotifen against histamine provocation therefore requires explanation.…”
Section: Drug Studymentioning
confidence: 99%
See 2 more Smart Citations
“…aneous weal and flare reactions evoked by allergen or compound 48/80 (Marks & Greaves, 1977;Johnson et al, 1984;Smith et al, 1980;Summers et al, 1981). Phillips et al (1983) examined the dose response relationships for H1-receptor inhibition of histamine (and allergen) induced cutaneous weal reactions by studying different concentrations of the H1-receptor antagonists administered intradermally. In order to define more clearly the effect of H2-receptor antagonism on cutaneous reactions mediated by histamine, we have employed a slight modification of the same technique to study the effect of ranitidine, an H2-receptor antagonist of between 4 and 10 times greater potency than cimetidine (Bradshaw et al, 1979;Daly et al, 1979;Brittain et al, 1981), over a 104 fold range of local tissue concentrations.…”
Section: Resultsmentioning
confidence: 99%